A rare case of low-dose methotrexate toxicity leading to skin and mucosal toxicity and invasive pulmonary mucormycosis: a case report - Luo, Lin; Wang, Lei; Zhao, Xiaoxia; Zhang, Na; Zhang, Yue; Xue, Xinggong; Li, Hui (Frontiers in Pharmacology, 2025)
Methotrexate is a potentially toxic antifolate antineoplastic and immunosuppressive agent that is widely used in tumor chemotherapy and autoimmune diseases (such as psoriasis). It is the cornerstone therapy for immune-mediated disorders worldwide. However, low-dose methotrexate therapy for psoriasis rarely causes toxicity. Here, we report a case of a patient with psoriasis who was treated with low-dose methotrexate for the first time. The patient developed severe mucosal ulcers and myelosuppression, leading to impaired immunity and invasive pulmonary mucormycosis. After treatment, the patient recovered and was discharged. It demonstrates that even low-dose methotrexate prescribed for psoriasis can induce severe toxicity. The case highlights the potential for low-dose methotrexate toxicity, suggesting that genetic polymorphisms may increase the risk of toxicity. The influence of genetic polymorphisms on methotrexate metabolism is highly variable. It is important to strengthen early monitoring in clinical practice, improve toxicity prediction models, and establish risk assessment systems for toxic drugs.